3D Direct Numerical Simulation on the Emergence and Development of Aeolian Sand Ripples - Huo, Xinghui; Dun, Hongchao; Huang, Ning; Zhang, Jie (Frontiers in Physics, 2021)
Sand surface subjected from continuous wind field exhibits a regular ripple surface. These aeolian sand ripples emerge and develop under the coupling effect between wind field, bed surface topology and sand particle transportation. Lots of theoretical and numerical models have been established to study the aeolian sand ripples since last century, but none of them has the capability to directly reproduce the 3D long-term development of them. In this work, a novel numerical model with wind-blow sand and dynamic bedform is established. The emergence and long-term development of sand ripples can be obtained directly. The statistical results extract from this model tallies with those deduced from wind tunnel experiments and field observations. A simplified bed surface particle size description procedure is used in this model, which shows that the particle size distribution makes an important contribution on sand ripples’ final steady state. This 3D bedform provides a more holistic view on the merging of small bumps before regular ripples’ formation. Analyzing on wind field results reveals an ignored development on particle dynamic threshold during the bedform deformation.